2018
DOI: 10.1098/rspb.2018.1168
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of corals and coralline algae to ocean acidification: physiological control of calcification under natural pH variability

Abstract: Ocean acidification is a threat to the continued accretion of coral reefs, though some undergo daily fluctuations in pH exceeding declines predicted by 2100. We test whether exposure to greater pH variability enhances resistance to ocean acidification for the coral sp. and coralline alga from two sites: one with low pH variability (less than 0.15 units daily; Shell Island) and a site with high pH variability (up to 1.4 pH units daily; Tallon Island). We grew populations of both species for more than 100 days u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
82
3
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 86 publications
(105 citation statements)
references
References 51 publications
(100 reference statements)
12
82
3
2
Order By: Relevance
“…Consistent with previous studies, pH cf was generally counter‐regulated with DIC cf (Cornwall et al, ; D'Olivo & McCulloch, ; McCulloch et al, ; Ross et al, ; Schoepf et al, ) thereby maintaining a tightly controlled chemical composition in the calcifying fluid at species‐dependent levels (McCulloch et al, ). Accordingly, changes in coral pH cf upregulation could be a mechanism aimed at maximizing and stabilizing both Ω cf and calcification rates.…”
Section: Discussionsupporting
confidence: 86%
“…Consistent with previous studies, pH cf was generally counter‐regulated with DIC cf (Cornwall et al, ; D'Olivo & McCulloch, ; McCulloch et al, ; Ross et al, ; Schoepf et al, ) thereby maintaining a tightly controlled chemical composition in the calcifying fluid at species‐dependent levels (McCulloch et al, ). Accordingly, changes in coral pH cf upregulation could be a mechanism aimed at maximizing and stabilizing both Ω cf and calcification rates.…”
Section: Discussionsupporting
confidence: 86%
“…The measured ν 1 FWHM was 9.5 cm −1 , compared to an expected FWHM of 8.2 cm −1 based on the Mg content (Perrin et al, 2016), leaving a "residual FWHM" of 1.3 cm −1 . Consistent with this result, three previous studies of coralline algae skeletons calculated residual FWHM in the same way and reported values ranging from approximately 0.3 to 1.6 cm −1 Cornwall et al, 2018;McCoy & Kamenos, 2018). The Amphisorus sp.…”
Section: In Vivo Raman Spectroscopy Of Marine Calcifying Organismssupporting
confidence: 80%
“…Raman spectroscopy has recently been applied to quantify the response of corals, coralline algae, and fish otoliths to simulated ocean acidification (Coll-Lladó, Giebichenstein, Webb, Bridges, & de la serrana, 2018;Comeau et al, 2018;Cornwall et al, 2018;DeCarlo et al, 2017;DeCarlo, Ren et al, 2018;Foster & Clode, 2016;Kamenos et al, 2013;Kamenos, Perna, Gambi, Micheli, & Kroeker, 2016). While these studies have revealed changes in both the mineralogy and disorder of calcified structures under ocean acidification, they have so far conducted Raman spectroscopy analyses of powders or made spot measurements on intact samples.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to differing ranges in temperature could explain some disparity in the responses reviewed here (e.g., Martone et al, 2010). Temperature variability can be extreme on some shallow coralline algal reefs (e.g., 14 • C daily, max 38 • C, excluding marine heatwave data) (Gruber et al, 2017;Cornwall et al, 2018). Therefore, estimating ambient temperatures for many of the collection sites was difficult, and we had to usually rely on a single value provided by authors, without knowing the summer maximum monthly mean or daily variability at collections sites.…”
Section: Recommended Protocols For Future Researchmentioning
confidence: 93%